Analisis Pemanfaatan Fly Ash Sebagai Pengganti Bata Beton untuk Meningkatkan Daya Kuat Tekan - Ade Triyanto, Romy; Napitupu, Robert; Juanda, Juanda (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Coal is an alternative energy source that is used for electricity generation and other needs. The coal burning process produces waste that is difficult to reprocess, one of which is fly ash. Fly ash waste has contents that resemble cement materials, such as silica, so it can be used as an additional material in making concrete bricks. This research aims to analyze the effect of using fly ash as an additional material on the compressive strength of concrete bricks and determine the highest and lowest compressive strength values ​​of various compositions of fly ash and sand. The full factorial method was used in this research to determine the number of specimens made. Variations in the composition of fly ash and sand applied were 10% : 60%, 20% : 50%, and 30% : 40%, with a fixed ratio of cement and water of 2 : 1. The drying process was carried out for 3 and 5 days. Testing Compressive strength was carried out on 6 specimens for each composition variation, with 3 repetitions on each specimen. The total specimens tested were 18. The test results showed that the specimen with a mixture of 10% fly ash: 60% sand and drying for 3 days (Specimen No. 1) produced the highest average compressive strength, namely: 56.91 kg/cm². Meanwhile, the lowest compressive strength was found in Specimen No.4 with a composition of 30% fly ash: 40% sand which was dried for 5 days, with an average compressive strength of 31.99 kg/cm².